Statin Use and Hepatocellular Carcinoma Risk: A Comprehensive Meta-Analysis and Systematic Review - Rafsanjani, Seyed Mahmood Reza Hashemi; Rahimi, Rasoul; Heidari-Soureshjani, Saeid; Darvishi, Mohammad; Adeli, Omid-Ali; Abbaszadeh, Saber (Recent Patents on Anti-Cancer Drug Discovery, 2025)
BackgroundHepatocellular Carcinoma (HCC) is a public health problem around the world. Several studies have investigated the association between statin use and the risk of HCC, however, more studies are needed in this field.ObjectivesThis systematic review and meta-analysis aimed to investigate the relationship between statin use and HCC risk.MethodsSystematic searches of Web of Science, Scopus, PubMed, Cochrane Library, Science Direct, and Embase were conducted for studies published between 1980 and September 2023. Meta-analyses were performed using Stata 15 with a significance level of 0.05.ResultsThe search retrieved 8,125 articles, of which 40 were included in the meta-analysis after applying eligibility criteria. The total sample was 5,732,948 participants, including 68,698 HCC cases. Statin use was associated with a 44% lower risk of HCC compared to non-use (RR 0.56, 95% CI 0.50–0.63, p < 0.001). The RR was 0.54 (0.42-0.69) in American countries, 0.52 (0.44-0.62) in Asian countries, and 0.63 (0.48-0.84) in European countries. The RR was 0.50 (0.42-0.60) in studies with a mean age <50 years and 0.61 (0.53-0.70) in studies with a mean age ≥50 years. No evidence of publication bias was found (Begg’s test p = 0.718).ConclusionThis meta-analysis found statin use is associated with a significantly lower HCC risk. Statins may be a promising preventive intervention against HCC.
Keywords: heterogeneity